Efeitos da linhaça marrom e dourada no perfil lipídico e inflamatório e na composição corporal de adolescentes com sobrepeso - Machado, Adriane Moreira (2013)
Flaxseed, rich in a-linolenic acid, lignans, and dietary fiber, is a promising food to reduce the risk of cardiovascular diseases. The objective of the current study was to evaluate the effects of brown and golden flaxseed on lipid profile, inflammation biomarkers, and body composition in overweight adolescents. The total of 75 overweight adolescents (33 boys and 42 girls) of 10 to 18 years of age was recruited. The volunteers were divided into 3 experimental groups (n=25). Group one received a daily portion of 28 g brown flaxseed (BF) from Monday to Friday in different food preparations, while group two received similar preparations containing golden flaxseed (GF), and the Control group (CG) received wheat bran in substitution to flaxseed, for 11 weeks. The amount of wheat bran was adjusted to match the fiber content of the flaxseed groups. Anthropometric, dietary and biochemical assays (total cholesterol and fractions, glucose, C-Reactive protein (CRP), and the cytokines: interleukines (IL)-1ß, IL6, IL-10, TNF-a, IFN-? and adiponectin) were carried out at the beginning and at the end of the study. The data were analyzed by ANOVA, paired t-test, Wilcoxon Signed and Kruskal-Wallis, using SPSS, version 19.0, at 5% significance. Sixty-one adolescents completed the study (BF=20, GF=20, CG=21). The average daily intake of flaxseed was approximately 14 g (BF= 14.4 g; GF=14.5 g). No significant changes were observed on the lipid profile and inflammation biomarkers (CPR, IL-6, IL-10, adiponectin and IFN- ?) at the end of the study. The boys of BF group showed a significant increase in their body weight, but with no change in body mass index (BMI), and the girls showed reduced glycemia and diastolic blood pressure. In both flaxseed groups (BF and GF) the intake of n-3 fatty acids and dietary fiber was increased, while the n-6:n-3 ratio was reduced with the intervention. The amount of flaxseed consumed may not have been sufficient to improve the lipid profile, inflammation biomarkers and body composition of the overweight adolescents, as reported in the literature. The intake of flaxseed, however, reduced glycemia and blood pressure, which indicates a potential benefit to reduce the risk of noncommunicable diseases.